Behaviour of SS-316L Hydroxyapatite Coated in Simulated Body Fluids - Helianty, Sri; Fadli, Ahmad; Silalahi, Yunita Magdalena; Barus, Yohana Dwi Nita (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Hydroxyapatite (HA) is a calcium phosphate mineral that closely resembles the inorganic component of natural bone. The incorporation of polycaprolactone (PCL) into HA enhances its mechanical strength, flexibility, and bioresorbability, producing composites with excellent biocompatibility and bioactivity in simulated body fluid (SBF). This study investigates the bioactivity and degradation behaviour of HA/PCL coatings on SS 316L stainless steel substrates. The relationships among coating thickness, shear strength, crystallinity, and pH variation in SBF were systematically examined. HA/PCL coatings were prepared using the dip-coating method and immersed in SBF at 37 °C for 7, 14, 21, and 28 days. Crystallinity and degradation characteristics were analysed using X-ray diffraction (XRD) and weight loss measurements. The results showed that HA/PCL-coated SS 316L exhibited noticeable weight loss after seven days of immersion due to Ca²⁺ ion release from the composite. Extended immersion led to increased HA crystallinity, indicating continued apatite formation and confirming the coating’s bioactive and biocompatible nature. Overall, the HA/PCL composite coating effectively enhances the bioactivity and provides controlled degradation of metallic implants, demonstrating strong potential for orthopaedic and dental biomedical applications